O uso dos computadores na Prática pedagógica: desafios para os professores da Escola Paroquial Cristo Rei. - Coelho, Marilene Ribeiro de Sousa (Universidade Federal do Tocantins, 2020)
This paper aims to reflect on the use of computers as a tool of new technologies in the pedagogical practices of teachers in a school in the city of Tocantinópolis, we will approach how the historical process of technologies in Brazil, discussion about the use and impacts of this technology at school, as well as reflect on the importance of teacher education to work with new technologies in their pedagogical practices. As theoretical basis we bring some authors, such as Moraes (2002), Nascimento (2007), Cox (2004), kenski (2012), among others. The discussions in this paper were about the use of new technologies (computer) at school and how the implementation process affects the institutional environment as a whole, in view of the challenges faced, the training and updating of educators to exercise their pedagogical practice with innovative methodologies that contribute to the formation of individuals. The study was necessary to understand how the process and / or the technological backlash occurred at school and how it directly affects the work of teachers today. It is important to have knowledge about these facts, which are present, and most of the time, go unnoticed for not having professionals prepared to use it, leaving education outdated. The methodology used for this work were bibliographic studies, readings, internet research and field research. And the instruments for the field research were questionnaires applied to some staff and teachers, observation in the physical space of the Cristo Rei Parish School. The results were obtained through the analysis, interpretation and tabulation of the data collected during the research. Noting that teachers are not fully equipped and prepared to use computers in their pedagogical practices.